Tingkat Eksistensi Elemen-Elemen Subak Sebagai Sistem Sosial (Kasus Pada Subak Munggu Tegal Lantang, Desa Pererenan, Kecamatan Mengwi, Kabupaten Badung) - PUDJA, PUTU CINTHYA WIRYANI; PUTRA, I GEDE SETIAWAN ADI; SUDARTA, WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol 6 No 1 (2017)DO - 10.24843/JAA.2017.v06.i01.p01, 2017)
The Existence Level of Subak Elements as Social Systems(A Case of Subak Munggu of Tegal Lantang, Village of Pererenan,Sub-District of Mengwi, Regency of Badung) Subak or organization of irrigation system is a world cultural heritage which must bepreserved, so that the existence of Subak should be maintained. The purpose of thisstudy was to determine the level of the existence of the elements of Subak as socialsystems that includes goals, beliefs, feelings or sentiments, norms, sanctions, positionand role, power, social rank, facilities, and area. The study took place in SubakMunggu Tegal Lantang by the number of respondents of 33 people. Data werecollected by interview and analyzed descriptively and qualitatively. The resultsshowed that the level of existence of elements of Subak as a social system was veryhigh with a score of 85,86%. It can be seen from the ten elements of a sociologicalapproach. Indicators of interest was very high with a score of 89,70%, confidencewas very high with a score of 89,70%, feeling was quite high with a score of 72,73%,norm was very high with a score of 89,09%, sanction was very high with a score of86,46 %, position and role were very high with a score of 90,15%, power was veryhigh with a score of 84,04%, social rank was very high with a score of 89,29%,facilities were high with a score of 77,17%, and area was very high with a score of90,30%.It is recommended that the Subak needs to strengthen some of the parametersof the weak indicators, i.e. the norms (awig awig, pararem) should be made in thewritten rules to suppress the land conversion to other uses, and it should pay moreattention to its problem such as the pest attacks.
Keywords: existence, cultural, social system, element, and sosial interaction